World-Renowned "Swiss" Pediatricians, Their Syndromes, and Matching Imaging Findings: A Historical Perspective - Laura M. Huisman; Thierry A. G. M. Huisman (MDPI AG, 2023)
The goal of this manuscript is to present and summarize several rare pediatric syndromes (Zellweger syndrome, Kartagener syndrome, Prader-Willi syndrome, Schinzel-Giedion syndrome, Fanconi anemia, Joubert-Boltshauser syndrome, Poretti-Boltshauser syndrome, and Langer-Giedion syndrome) who have been named after luminary "Swiss" physicians (pediatricians, pediatric neurologists, or pediatric radiologists) who recognized, studied, and published these syndromes. In this manuscript, a brief historical summary of the physicians is combined with the key clinical symptoms at presentation and the typical imaging findings. This manuscript is not aiming to give a complete comprehensive summary of the syndromes, nor does it ignore the valuable contributions of many "Swiss" scientists who are not included here, but focuses on several rare syndromes that benefit from imaging data.